Analyzing the Influence of User Generated Content (UGC) on Social Media Platforms in Travel Planning - Rathore, Sheetal (Turizam, 2020)
In recent years Social Media (SM) platforms is becoming highly significant for tourism industry as a medium for information exchange and communication platforms for tourists and travelers. Tourists are using Web 2.0 platforms to plan their travel, book hotels, confirm and cancel reservations, enquire about packages and itineraries, to read reviews posted by other travelers and also to share their travel experiences by posting reviews, comments, ratings, photographs etc. with others. The purpose of this study is to determine the influence of user generated content on social media platforms in travel planning of tourists in Udaipur, India. This study analysis opinion of tourists regarding benefits of social media and travel material posted on various social media platforms and to draw factors that are helpful in influencing the use of information through social media. To fulfill the objectives, primary data was collected by using judgmental sampling method and 5-point Likert type scale through structured questionnaire. A sample of 309 respondents who visited Udaipur as tourist during the period of early October 2017 to end of March 2018 was surveyed. Using descriptive statistics and factor analysis results were presented and explained. The findings revealed that tourists have positive opinion towards online reviews and travel material posted on social sites. Majority of the tourist respondents opined that online reviews, rating and comments etc. regarding travel destination, hotels, food and climate etc. help in their travel planning and travel related decisions. The results of factor analyses demonstrated that three factors namely; social media ease and trust, social media risk reduction and helpfulness and social media enhance joy and excitement were considered helpful in influencing the use of information through social media sites.